Palliative Care in End-Stage Liver Disease Patients Awaiting Liver Transplantation: Review - Silva,Sara Vieira (2020)
Introduction: End-stage liver disease (ESLD) is the advanced phase of most liver diseases. The cure is liver transplantation (LT), only available for a minority of patients. This review summarizes the evidence regarding palliative care (PC) in ESLD patients awaiting LT. Methods: Review of the literature available in Medline, Scopus and Web of Knowledge, with keywords ESLD and PC. Results: Fifteen of the 230 articles reviewed met the inclusion criteria. Ten main themes were addressed: symptom burden; perspectives of life-sustaining treatment and comfort for patients, families and health professionals; goals of care discussions; patient and family needs; quality of life; PC and survival; referral to PC, barriers and opportunities; integration of PC; outpatient care and cost-effectiveness analysis. The referral of patients to PC was only evaluated in a few studies, all of which reported low referral rates. Better knowledge of how PC professionals can support other professionals was considered important, and also better ways to integrate PC were considered essential. Conclusion: ESLD patients awaiting LT have a significant need for PC and, despite the insufficient response, were reported to benefit from this type of care. Future research is essential to determine the means to overcome barriers and better integrate PC for ESLD patients awaiting LT.